Assessing the Potential to Expand Community College Baccalaureate Programs in Texas - Daugherty, Lindsay (RAND Corporation, 2014)
To inform decisions about whether community college baccalaureate degree programs should be expanded in Texas, this report assesses unmet workforce-development needs in nursing and four applied science occupations: computer and information technology, management of fire sciences, management of production/operations technicians, and health information technology.